ANALISIS PERBANDINGAN DEBT TO EQUITY RATIO DAN CURRENT RATIO PADA PT. TELEKOMUNIKASI INDONESIA TBK DAN PT INDOSAT TBK TAHUN 2015-2024 - Saputra, Egis; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to analyze and compare the Debt to Equity Ratio (DER) and Current Ratio (CR) of PT Telkom Indonesia (Persero) Tbk and PT Indosat Tbk during the 2015–2024 period. This study employed a quantitative method with a comparative descriptive approach. The data used were annual financial statements obtained from the official websites of the companies. Data analysis techniques included descriptive statistics, Shapiro-Wilk normality test, and independent sample t-test using IBM SPSS Statistics 26. The results indicate that PT Indosat Tbk has a higher DER than PT Telkom Indonesia Tbk, while PT Telkom Indonesia Tbk has a higher and more stable CR than PT Indosat Tbk. The independent sample t-test results show significant differences in DER and CR between the two companies during the study period.